2016
DOI: 10.14710/mkts.v21i1.11225
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Land Subsidence terhadap Genangan Banjir dan Rob di Semarang Timur

Abstract: Inundation of flood and rob (flood due to high tides) in Semarang City is increase wtithin area and depth. It be more seroius condition because of land subsisdence that happened in coastal area of Semarang City. This research is foccused on prediction and mapping of inundation flood and rob due to land subsidence effect in East Semarang, especially Tenggang Watershed and Sringin Watershed. On this research, data analysis including analysis of land subsidence, analysis of hydrological data, analysis of flood di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Some cities and settlements in Indonesia, even in the world, are geographically located and directly face the coastal areas (Ji et al 2010;Crowell 2010;Lin et al 2013;Purnama et al 2015;Menèndez 2019;Triana & Hidayah 2020), while changes on global climate in coastal areas (Ji et al 2010;Pappone et al 2012;Sihombing et al 2012, Condon et.al 2012Rao et.al 2020) has resulted in increasing losses and damages (Bhattacharya 2011;Wang 2014;McGuire 2018;Purnama et al 2015). Semarang city, as the center of trade, industry, and government, cannot resist from the threat of climate change as well, especially the tidal flood disaster (Marfai et al 2008;Kahar et al 2010;Pujiastuti 2015).…”
Section: Research Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Some cities and settlements in Indonesia, even in the world, are geographically located and directly face the coastal areas (Ji et al 2010;Crowell 2010;Lin et al 2013;Purnama et al 2015;Menèndez 2019;Triana & Hidayah 2020), while changes on global climate in coastal areas (Ji et al 2010;Pappone et al 2012;Sihombing et al 2012, Condon et.al 2012Rao et.al 2020) has resulted in increasing losses and damages (Bhattacharya 2011;Wang 2014;McGuire 2018;Purnama et al 2015). Semarang city, as the center of trade, industry, and government, cannot resist from the threat of climate change as well, especially the tidal flood disaster (Marfai et al 2008;Kahar et al 2010;Pujiastuti 2015).…”
Section: Research Backgroundmentioning
confidence: 99%
“…Ongoing development as well as industrial and trade expansion that neglect the sustainability of natural resources and the carrying capacity of the environment (especially soil conditions and the balance of groundwater resources) cause land subsidence Khoirunisa et al 2015;Pujiastuti et al 2015;Kasfari et al 2018, Rao 2020 and result in land below sea level (Nugraha et al 2015;Kuehn et al 2010). The ongoing global warming also affects sea level rise Ward et al 2011;Nurhendro & Marfai 2016) which has implications for the widening level of tidal flood inundation in lowland areas (Gallien et al 2013;Astuti et al 2020).…”
Section: Research Backgroundmentioning
confidence: 99%
“…This location is also per the Spatial Plan. However, the area around the coastal area of the eastern part of the city of Semarang, especially in the District of Genuk, including Terboyo, experiences the risk of rob and flooding caused by land subsidence (Pujiastuti, Suripin, & Syafrudin, 2015). This condition is suspected because of the high use of groundwater that is not balanced by the replenishment of balanced groundwater causing a decrease in groundwater level (Asdak, 1995).…”
Section: Administration (Location Selection and Preparation)mentioning
confidence: 99%
“…In recent decades, several countries have faced the issue of mangrove damage as a major threat to the sustainability of coastal ecosystems (Gedan et al, 2011;Osland et al, 2012;Nortey et al, 2016;Meng et al, 2017). The degradation of coastal ecosystems, which has an impact on the failure of sustainable coastal management, also occurs in Indonesia, especially on the coast of Semarang City (Suhelmi, 2012;Pujiastuti et al, 2015). Environmental degradation, the emergence of slum settlements, sea water intrusion that interferes with the availability of clean water, water and air pollution are the bad faces of the central government in Central Java (Pratikno et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, excessive groundwater extraction (Ikhsyan et al, 2017) also triggers land subsidence (Yuwono et al, 2013;Maarif et al, 2015). Several studies showed that the decline that occurs on the north coast is very high, reaches 5.16 cm-5.58 cm/year causing the land to decline further so that tidal flooding is increasingly spreading to ponds and residential areas (Wirasatriya et al, 2005;Pujiastuti et al, 2015;Islam et al, 2017;Ondara et al, 2020).…”
Section: Introductionmentioning
confidence: 99%